2013
DOI: 10.1007/s00216-013-7074-z
|View full text |Cite
|
Sign up to set email alerts
|

Adduct supported analysis of γ-hydroxybutyrate in human serum with LC-MS/MS

Abstract: To avoid the detection of small fragmentation products of γ-hydroxybutyrate (GHB), a liquid chromatography-tandem mass spectrometry GHB quantification method in human serum supported by adduct formation was developed and validated. The continuous infusion of GHB/GHB-D6 made the identification of two adducts possible and GHB/GHB-D6 sodium acetate adduct fragmentation was used as target mass transition. A Luna 5 μm C18 (2) 100 A, 150 mm × 2 mm analytical column and elution with a programmed flow of the mobile ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…In comparison to the LC/MS/MS method for GHB analysis in human serum on the basis of analyte adduct formation with the components of the mobile phase [6], a better LOD/LOQ could be achieved with the MS3 method presented here. The results of the validation experiments demonstrated, that the presented analytical strategy based on LC-MS/MS/MS and the GHB adduct formation/fragmentation process can be applied in the field of forensic toxicology and clinical chemistry as an alternative to common GHB analytical methods in human serum.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…In comparison to the LC/MS/MS method for GHB analysis in human serum on the basis of analyte adduct formation with the components of the mobile phase [6], a better LOD/LOQ could be achieved with the MS3 method presented here. The results of the validation experiments demonstrated, that the presented analytical strategy based on LC-MS/MS/MS and the GHB adduct formation/fragmentation process can be applied in the field of forensic toxicology and clinical chemistry as an alternative to common GHB analytical methods in human serum.…”
Section: Resultsmentioning
confidence: 86%
“…To ensure the best comparison between GHB detection with MS2 and MS3 the chromatographic conditions applied were the same as presented in the MS2 analytical method published earlier [6]. Therefore, the separation was performed with a Luna 5 m C18 (2) 100Å, 150 mm × 2 mm column (Phenomenex, Aschaffenburg, Germany) and the elution with a mobile phase consisting of 10% A (H 2 O/methanol = 95/5, v/v) and 90% B (H 2 O/methanol = 3/97, v/v), both with 10 mM ammonium acetate and 0.1% acetic acid (pH = 3.2).…”
Section: Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, it has been demonstrated that controlled analyte adduct formation is an interesting alternative (and sometimes even the only effective possibility) for the LC-MS n quantification of relevant small-molecule drugs [7,9,[11][12]15]. Although it was already demonstrated that analyte adducts can be observed for numerous drugs with appropriate molecular structure and therefore the possibilities for its application can be defined as wide, analyte adduct formation seems to be applicable only if the conventional strategy of LC-MS n analysis does not bring the expected results [17].…”
Section: Resultsmentioning
confidence: 99%
“…2 applications To avoid the detection of small ion fragments, an analyte adduct formation/fragmentation strategy was developed for the generation of bigger ion fragments that could be used for LC-MS 2 analysis of γ-hydroxybutyrate (GHB), which was used as a model drug [7]. A GHB sodium acetate adduct ion was described as a target, of which the fragmentation was the basis for LC-MS 2 analysis to avoid the detection of ions smaller than 85 Da as described previous [8].…”
Section: Generation Of Bigger Ion Fragments Of Small-molecule Drugs Wmentioning
confidence: 99%